Congenital Hypopituitarism During the Neonatal Period: Epidemiology, Pathogenesis, Therapeutic Options, and Outcome - Bosch i Ara, Laura; Katugampola, Harshini; Dattani, Mehul T. (Frontiers in Pediatrics, 2021)
Congenital hypopituitarism (CH) is characterised by a deficiency of one or more pituitary hormones. The pituitary gland is a central regulator of growth, metabolism and reproduction. The anterior pituitary produces and secretes growth hormone, adrenocorticotropic hormone, thyroid-stimulating hormone, follicle-stimulating hormone, luteinizing hormone and prolactin. The posterior pituitary hormone secretes antidiuretic hormone and oxytocin. Epidemiology: The incidence is 1 in 4000 – 1 in 10000. The majority of CH cases are sporadic; however, a small number of familial cases have been identified. In the latter, a molecular basis has frequently been identified. Between 80-90% of CH cases remain unsolved in terms of molecular genetics. Pathogenesis. Several transcription factors and signalling molecules are involved in the development of the pituitary gland. Mutations in any of these genes may result in CH including HESX1, PROP1, POU1F1, LHX3, LHX4, SOX2, SOX3, OTX2, PAX6, FGFR1, GLI2 and FGF8. Over the last 5 years, several novel genes have been identified in association with CH, but it is likely that many genes remain to be identified as the majority of patients with CH do not have an identified mutation. Clinical manifestations. Genotype-phenotype correlations are difficult to establish. There is a high phenotypic variability associated with different genetic mutations. The clinical spectrum includes severe midline developmental disorders, hypopituitarism (in isolation or combined with other congenital abnormalities), and isolated hormone deficiencies. Diagnosis and treatment. Key investigations include MRI and baseline and dynamic pituitary function tests. However, dynamic tests of GH secretion cannot be performed in the neonatal period, and a diagnosis of GH deficiency may be based on auxology, MRI and a low growth factor concentrations. Once a hormone deficit is confirmed, hormone replacement should be started. If onset is acute with hypoglycaemia, cortisol deficiency should be rapidly treated, as should TSH deficiency. This review aims to give an overview of CH and to assist both neonatologists and endocrinologists in the management of this complex condition